Neutropenic Enterocolitis in Critically Ill Patients: Spectrum of the Disease and Risk of Invasive Fungal Disease. Issue 5 (May 2019) - Duceau, Baptiste; Picard, Muriel; Pirracchio, Romain; Wanquet, Anne; Pène, Frédéric; Merceron, Sybille; Mokart, Djamel; Moreau, Anne-Sophie; Lengliné, Etienne; Canet, Emmanuel; Lemiale, Virginie; Mariotte, Eric; et al.
Abstract : Objectives: Neutropenic enterocolitis occurs in about 5.3% of patients hospitalized for hematologic malignancies receiving chemotherapy. Data from critically ill patients with neutropenic enterocolitis are scarce. Our objectives were to describe the population of patients with neutropenic enterocolitis admitted to an ICU and to investigate the risk factors of invasive fungal disease. Design: A multicentric retrospective cohort study between January 2010 and August 2017. Setting: Six French ICUs members of the Groupe de Recherche Respiratoire en Onco-Hématologie research network. Patients: Adult neutropenic patients hospitalized in the ICU with a diagnosis of enteritis and/or colitis. Patients with differential diagnosis ( Clostridium difficile colitis, viral colitis, inflammatory enterocolitis, mesenteric ischemia, radiation-induced gastrointestinal toxicity, and Graft vs Host Disease) were excluded. Interventions: None. Measurement and Main Results: We included 134 patients (median Sequential Organ Failure Assessment 10 [8–12]), with 38.8% hospital mortality and 32.1% ICU mortality rates. The main underlying malignancies were acute leukemia ( n = 65, 48.5%), lymphoma ( n = 49, 36.6%), solid tumor ( n = 14, 10.4%), and myeloma ( n = 4, 3.0%). Patients were neutropenic during a median of 14 days (9–22 d). Infection was documented in 81 patients (60.4%), including an isolated bacterial infection in 64 patients (47.8%), an isolated fungal infection in nine patients (6.7%), and a coinfection with both pathogens in eight patients (5.0%). Radiologically assessed enteritis (odds ratio, 2.60; 95% CI, 1.32–7.56; p = 0.015) and HIV infection (odds ratio, 2.03; 95% CI, 1.21–3.31; p = 0.016) were independently associated with invasive fungal disease. Conclusions: The rate of invasive fungal disease reaches 20% in patients with neutropenic enterocolitis when enteritis is considered. To avoid treatment delay, antifungal therapy might be systematically discussed in ICU patients admitted for neutropenic enterocolitis with radiologically assessed enteritis. Abstract : Supplemental Digital Content is available in the text.